CALCULATION OF THE TERRITORY RECREATION ATTRACTIVENESS USING FUZZY LOGIC - Vyklyuk, Yaroslav; Artemenko, Olga (International Journal of Computing, 2014)
In this paper the calculation method of the territory tourist attractiveness aggregated potential is offered on the base of fuzzy logic taking into account the factor of seasonality. The potentials of tourist attractiveness are found for the basic tourist recreation systems of the Chernivtsi region.